Attenuating effect of Polygala tenuifolia Willd. seed oil on progression of MAFLD - Xin, Meiling; Wang, Hanlin; Wang, Meng; Yang, Bendong; Liang, Shufei; Xu, Xiaoxue; Dong, Ling; Cai, Tianqi; Huang, Yuhong; Wang, Qing; Wang, Chao; Cui, Yuting; et al. (Frontiers in Pharmacology, 2023)
Introduction: Metabolic-associated fatty liver disease (MAFLD) is a common chronic metabolic disease that seriously threatens human health. The pharmacological activity of unsaturated fatty acid-rich vegetable oil interventions in the treatment of MAFLD has been demonstrated. This study evaluated the pharmacological activity of Polygala tenuifolia Willd, which contains high levels of 2-acetyl-1,3-diacyl-sn-glycerols (sn-2-acTAGs). Methods: In this study, a mouse model was established by feeding a high-fat diet (HFD, 31% lard oil diet), and the treatment group was fed a P. tenuifolia seed oil (PWSO) treatment diet (17% lard oil and 14% PWSO diet). The pharmacological activity and mechanism of PWSO were investigated by total cho-lesterol (TC) measurement, triglyceride (TG) measurement and histopathological observation, and the sterol regulatory element-binding protein-1 (SREBP1), SREBP2 and NF-κB signaling pathways were evaluated by immunofluorescence and Western blot analyses. Results: PWSO attenuated the increases in plasma TC and TG levels. Furthermore, PWSO reduced the hepatic levels of TC and TG, ameliorating hepatic lipid accumulation. PWSO treatment effectively improves the level of hepatitic inflammation, such as reducing IL-6 levels and TNF-α level. Discussion: PWSO treatment inactivated SREBP1 and SREBP2, which are involved in lipogenesis, to attenuate hepatic lipid accumulation and mitigate the inflammatory response induced via the NF-κB signaling pathway. This study demonstrated that PWSO can be used as a relatively potent dietary supplement to inhibit the occurrence and development of MAFLD.